Concentrations of sulphur and trace elements in subarctic soils and mosses in relation to geothermal power plants at Hengill, Iceland – ecological implications. (September 2021) - Mutia, Thecla M.; Fridriksson, Thrainn; Magnússon, Sigurdur H.; Jónsdóttir, Ingibjörg Svala
Highlights: Element concentrations in moss and soil differed between two power plants in South West Iceland. Moss growth was greater at the power plant where moss element concentrations were high. There are some trends of high element deposition in moss and soil around the Hengill geothermal power plants. Higher concentrations of S, As, B, Sb and Hg in moss and soil around the Hengill geothermal power plants did not cause negative effects on moss health. Abstract: Amidst the globally accelerated plans to increase geothermal energy utilization, knowledge of ecological responses to power plant emissions is limited. The aim of this study is to investigate ecosystem accumulation of elements emitted from power plants in the Hengill geothermal field in Southwest Iceland, in relation to patterns of plant growth and health. The moss Racomitrium lanuginosum was used as a bio-indicator, a dominating plant in our study areas. Concentrations of sulphur, arsenic, boron, antimony, and mercury in soil and shoots of R. lanuginosum, were determined, and growth and other moss characteristics (moss damage, physiology and mat depth) assessed at different distances and directions from two geothermal power plants, Hellisheidi (303 MWe, operated since 2006) and Nesjavellir (120 MWe, operated since 1990). Higher concentrations of these elements were detected around Hellisheidi than Nesjavellir. Sulphur, antimony, and mercury concentrations in moss decreased with increasing distance from the power plant around Nesjavellir, while arsenic concentrations increased with increasing distance away and boron concentrations were relatively low, below detection. Similar trends for sulphur and antimony followed in soils. Arsenic concentrations in soil on the other hand, increased with increasing distance from the Nesjavellir power plant while boron concentrations were, below detection limit except at 250 m downwind and at 1000 m and 4000 m upwind. At Hellisheidi, sulphur and boron concentrations, in moss decreased with increasing distance away from the power plant and showed an opposite trend in soil. Arsenic, antimony and mercury concentrations in moss showed a general increase in concentrations with increasing distance away from the power plant; while in soil, trace element concentrations did not change significantly with distance, and there were no clear patterns related to the direction of prevailing winds. On average, moss growth and other moss trait values were higher at Hellisheidi than Nesjavellir. At Nesjavellir, moss mat depth and biomass moss response variables increased with increasing distance away and were greater upwind than downwind; while shoot turnover (%) and chlorophyll concentration decreased with increasing distance away from the power plant and did not vary with direction. Moss shoot length did not vary with distance but showed a decrease downwind. At Hellisheidi, trends were non-linear with distance, however biomass increase was the only response variable significantly higher downwind than upwind: other variables did not vary with direction. The frequency of moss damage was quite low around both power plants. We thus conclude that emitted sulphur from the geothermal power plants is deposited in the surrounding ecosystem and has so far no clear indications of harmful effects. In addition, the emerging patterns of arsenic, boron, antimony and mercury concentrations in the ecosystem were not clear to indicate deposition from the geothermal power plants and there were no related harmful effects. Nonetheless, further long-term monitoring of potential environmental impacts is advised. We recommend experimental studies to establish in detail if and how different levels of sulphur deposition may affect ecosystems for appropriate mitigation.